Epidemiology of Acanthamoeba species in water treatment works in England - Shanmuganathan, Vydeki (2019)
Acanthamoeba spp. are often described as emerging opportunistic protozoan pathogens. Infection is associated with two main clinical diseases: Acanthamoeba keratitis (AK), and infection of the central nervous system in immunocompromised individuals, granulomatous amoebic encephalitis (GAE). The risk factors for AK are contaminated water and wearing contact lenses. Although the occurrence of Acanthamoeba spp. in tap water is well documented, its original source, whether from the public water supply or more locally, within domestic properties, is unknown.